The long-term course of the annual total sunshine duration in Europe and changes in the phases of the thermohaline circulation in the North Atlantic (1901–2018). - Marsz, Andrzej A.; Styszyńska, Anna; Matuszko, Dorota (Quaestiones Geographicae, 2023)
The current study was based on sunshine duration data from 13 European stations during 1901–2018. It was found that the variability in the annual total sunshine duration (SD) over Europe is related to the variability in the component of the surface thermohaline circulation in the North Atlantic (NA THC). Positive NA THC phases (the condition of the ‘warm’ North Atlantic) correspond to the periods of increased SD (brightening), while negative phases correspond to the periods of decreased SD (dimming). These relationships remain stable and statistically significant. The mechanism of these relationships is based on the influence of weakened or enhanced heat flow from the ocean to the atmosphere on the course of the mid-tropospheric circulation processes. In periods of positive thermohaline circulation in the North Atlantic (NA THC) phases, the share of long waves (macrotype W according to the Wangengejm–Girs classification) increases, with the occurrence of which the frequency of anticyclonic weather over Europe in creases, whereas in the periods of negative NA THC phases, the share of shorter waves (macrotypes E and C) increases, with the occurrence of which the frequency of cyclonic (frontal) weather over Europe increases. It is characterised by increased layer cloud cover, limiting the SD. Thus, along with changes in the thermal condition of the North Atlantic, the structure of cloud cover over Europe changes and becomes a factor regulating long-term changes in the annual total SD.